Photosynthetic control of Arabidopsis leaf cytoplasmic translation initiation by protein phosphorylation. - Edouard Boex-Fontvieille (Public Library of Science (PLoS), 2013)
Photosynthetic CO2 assimilation is the carbon source for plant anabolism, including amino acid production and protein synthesis. The biosynthesis of leaf proteins is known for decades to correlate with photosynthetic activity but the mechanisms controlling this effect are not documented. The cornerstone of the regulation of protein synthesis is believed to be translation initiation, which involves multiple phosphorylation events in Eukaryotes. We took advantage of phosphoproteomic methods applied to Arabidopsis thaliana rosettes harvested under controlled photosynthetic gas-exchange conditions to characterize the phosphorylation pattern of ribosomal proteins (RPs) and eukaryotic initiation factors (eIFs). The analyses detected 14 and 11 new RP and eIF phosphorylation sites, respectively, revealed significant CO2-dependent and/or light/dark phosphorylation patterns and showed concerted changes in 13 eIF phosphorylation sites and 9 ribosomal phosphorylation sites. In addition to the well-recognized role of the ribosomal small subunit protein RPS6, our data indicate the involvement of eIF3, eIF4A, eIF4B, eIF4G and eIF5 phosphorylation in controlling translation initiation when photosynthesis varies. The response of protein biosynthesis to the photosynthetic input thus appears to be the result of a complex regulation network involving both stimulating (e.g. RPS6, eIF4B phosphorylation) and inhibiting (e.g. eIF4G phosphorylation) molecular events.